Pengabdian Dan Pemberdayaan Keluarga Duafa - Moh. Iqbal Amirullah; Farhad Farhad; Alfarisi Alfarisi; Mulkan Habibi (Lembaga Pengembangan Kinerja Dosen, 2024)
The community service and empowerment program for underprivileged families aims to improve the welfare and quality of life of poor families through a series of activities focused on education, health, and economic empowerment. The approach used involves collaboration between the community, the government, and non-governmental organizations (NGOs). In this program, underprivileged families are provided access to various skills training, business capital assistance, as well as free health and education services. Program evaluation shows a significant increase in family income, a reduction in school dropout rates, and improvements in the health conditions of participants. These results indicate that a holistic and participatory approach can effectively address poverty issues and enhance the welfare of underprivileged families. However, for the program's sustainability, continuous support from various parties, as well as regular monitoring and evaluation, is required.